TAX REFORM AND ITS IMPACTS ON ENVIRONMENTAL POLICY: A STUDY OF TAX EVASION OF IPVA FOR ELECTRIC CARS IN SÃO PAULO - de Giorge Cerqueira , Homero (Revista Gênero e Interdisciplinaridade, 2025)
This paper aims to analyze the impacts of the Tax Reform on environmental policy and the Brazilian economy, with an emphasis on tax evasion of the Motor Vehicle Property Tax (IPVA) in relation to electric cars in the State of São Paulo. With the growth of environmental concerns and the increasing adoption of electric vehicles, the tax reform offers an opportunity to rethink tax laws and encourage them. However, tax evasion associated with these vehicles represents a significant challenge, requiring a detailed investigation of the factors that contribute to this situation. Thus, the study seeks to understand how the reform can impact both tax collection and sustainable practices in urban mobility, promoting a discussion on the need for more effective public policies and the promotion of a greener economy. The approval of the Tax Reform (Constitutional Amendment No. 132/2023) represented a historic legal milestone in Brazil. The changes promoted by this constitutional amendment had repercussions on both environmental policy and the country’s economy. In view of these facts, the objective of this study was to analyze how these changes influenced the Public Treasury and the behavior of taxpayers in relation to tax incentives granted in the search for an ecologically balanced environment. To this end, the hypothetical-deductive method was used in the search for solutions to a legal gap that has as its central point the absence of a Federal Complementary Law, providing for general rules of the Tax on Motor Vehicle Ownership (IPVA). In this sense, the analysis of a specific case involving the State of São Paulo was used as a basis. The results of the case study suggest that, under the current rules of the national legal system, taxpayers are prone to commit crimes against the tax system in order to take advantage of the tax benefits arising from the new environmental policy. It is concluded that, in order to make the environmental tax incentive policy more effective, it is necessary to enact a Federal Complementary Law on general rules of the IPVA. In addition, it is necessary to strengthen the legislation that deals with tax crimes and establish a new ethical standard in the country.